Exploring human-animal interactions beyond academic research: A rapid review of grey literature - Siyu Ru; Daniel Villarreal Hernandez; Szymon Parzniewski; Haorui Wu (Animal Welfare, 2025)
Increasing recognition of the diverse benefits of human-animal interactions (HAIs) has propelled related studies. Although most of the benefits have been illustrated by academic literature (e.g. journal articles, academic theses, and project reports), the grey literature contributes to a comprehensive understanding of HAIs and offers new perspectives, informing prospective research, practices, and policies. Adapting the Systematic Reviews and Meta-Analyses (PRISMA) approach, this rapid review examined 151 articles covering HAIs from 2016–2022. The univariate analysis results revealed that the sources covered various animal species (e.g. dogs, cats, birds), types of animals (e.g. companion animals, therapy animals, zoo animals), and vulnerable populations (e.g. older adults, people with disabilities). HAIs could be found across different settings, such as households, schools, healthcare facilities, and more. The thematic analysis identified three primary categories associated with HAIs’ benefits in public education: (1) HAIs benefit the well-being of individuals, families, and animals; (2) HAIs promote prosocial behaviours and community development; and (3) HAIs improve disaster preparedness and response. The results highlight the multifaceted positive influences of HAIs on human well-being, animal welfare, and building healthy and resilient communities. Grey literature plays an essential role in knowledge mobilisation through public education, promoting the interconnectedness between human well-being and animal welfare.